Submergence rice cultivation in southern Bangladesh: farmers opinion and adaptations practices - Biswas, AKM Abdul Ahad; Mamun, Md. Abdullah-Al; Rahman, Md. Saifur; Sattar, Md. Abdus; Zaman, AKM Mostafa (International Journal of Environment, 2015)
Rice productivity in coastal Bangladesh is lower than the national average and total coastal area is considered to be submergence-prone and higher vulnerable in July to January cropping season. The selected study areas are Kalapara and Patuakhali Sadar Upazila that are too vulnerable to agriculture practices. Field survey was conducted during 01st June to 30th July, 2015 to investigate the impact of submergence on Aman rice cultivation (ARC), existing adopted local adaptation practices with impacts and options to address the submergence problem. Primary data was collected through Focus Group Discussion (FGD), Individual Interview and Key Informant Interview methods and secondary data was collected from different secondary sources. A well-structured pretested questionnaire schedule was developed keeping in mind the objectives and variables under this study. After cyclone SIDR and AILA devastation, the rate of traditional ARC is decreasing every year and in 2015 it was 26.51%. Recently farmers have adopted new cropping practices and strategies like modern ARC in Aman season as single crop; Boro-Aus-Aman season as triple crop and Aus-Aman season as double crop are practicing. Approximately all farmers have adopted to grow stress tolerant rice varieties (STRV); farmer’s curiosities to familiar with and to have the STRV are encouraging. Farmers were fully adopted BRRIdhan52 rice cultivation with positive perceptions of higher yield and lower production cost. Therefore it can be concluded that the intensity of adoption of adaptation and mitigation measures are significantly influenced positively by the STRV yield capability; farmer’s participation in intervention programs; livelihood diversification; frequency of extension personnel contact; submergence and inundation characteristics; tolerance attributes of STRV and availability of STRV cultivation information.International Journal of Environment Vol.4(4) 2015: 100-113